A Kinase Anchor Protein 4 Is Vulnerable to Oxidative Adduction in Male Germ Cells - Nixon, Brett; Bernstein, Ilana R.; Cafe, Shenae L.; Delehedde, Maryse; Sergeant, Nicolas; Anderson, Amanda L.; Trigg, Natalie A.; Eamens, Andrew L.; Lord, Tessa; Dun, Matthew D.; De Iuliis, Geoffry N.; Bromfield, Elizabeth G. (Frontiers in Cell and Developmental Biology, 2019)
Oxidative stress is a leading causative agent in the defective sperm function associated with male infertility. Such stress commonly manifests via the accumulation of pathological levels of the electrophilic aldehyde, 4-hydroxynonenal (4HNE), generated as a result of lipid peroxidation. This highly reactive lipid aldehyde elicits a spectrum of cytotoxic lesions owing to its propensity to form stable adducts with biomolecules. Notably however, not all elements of the sperm proteome appear to display an equivalent vulnerability to 4HNE modification, with only a small number of putative targets having been identified to date. Here, we validate one such target of 4HNE adduction, A-Kinase Anchor Protein 4 (AKAP4); a major component of the sperm fibrous sheath responsible for regulating the signal transduction and metabolic pathways that support sperm motility and capacitation. Our data confirm that both the precursor (proAKAP4), and mature form of AKAP4, are conserved targets of 4HNE adduction in primary cultures of post-meiotic male germ cells (round spermatids) and in mature mouse and human spermatozoa. We further demonstrate that 4HNE treatment of round spermatids and mature spermatozoa results in a substantial reduction in the levels of both proAKAP4 and AKAP4 proteins. This response proved refractory to pharmacological inhibition of proteolysis, but coincided with an apparent increase in the degree of protein aggregation. Further, we demonstrate that 4HNE-mediated protein degradation and/or aggregation culminates in reduced levels of capacitation-associated phosphorylation in mature human spermatozoa, possibly due to dysregulation of the signaling framework assembled around the AKAP4 scaffold. Together, these findings suggest that AKAP4 plays an important role in the pathophysiological responses to 4HNE, thus strengthening the importance of AKAP4 as a biomarker of sperm quality, and providing the impetus for the design of an efficacious antioxidant-based intervention strategy to alleviate this dysfunction.